Introduction to relational data bases and SQL Programming - Christopher Allen (McGraw Hill Technology Education, 2004)
Berisi : Oracle9i Preinstallation Requirements, Installation Issues, Upgrade Issues, Product-Ralated Issues, Documentation Accessbility, Oracle9i Documentation Links